Relative Contributions of Base Stacking and Electrostatic Repulsion on DNA Nicks and Gaps - Harris, Paul D; Hamdan, Samir M; Habuchi, Satoshi (The journal of physical chemistry. B, 2020)
In duplex DNA, the continuous sugar phosphate backbones prevent the double helix from significant bending, but breaks in the duplex such as nicks, gaps, and flaps present points at which significant bending is possible. The conformational dynamics of these aberrant structures remains poorly understood. Two factors can maintain the duplexlike conformation of these aberrant structures, these being the hydrophobic and aromatic stacking interactions of the nucleobases, and the electrostatic repulsion of the negatively charged backbones. Using confocal single-molecule Förster resonance energy transfer on nicked and gapped DNA structures, we compare the relative contributions of these two factors by modulating the electrostatic repulsion through mono- and divalent cation concentrations. Base stacking interactions dominate the dynamics of nicked DNA, making it behave essentially like duplex DNA. Gapped structures have weaker base stacking and thus backbone electrostatic repulsion becomes important, and shielding from cations results in an average increase in bending around the gap. This bending of gapped structures could be interpreted by increased flexibility of unstacked structures, transient unstacking events, or a combination of the two. Burst variance analysis (BVA) and analysis by photon-by-photon hidden Markov modeling (H2MM), methods capable of detecting submillisecond dynamics of single molecules in solution, only revealed a single state, indicating that dynamics are occurring at time scales shorter than microseconds.